Factor structure and validity of the dyadic coping inventory–Bahasa Indonesia. Issue 4 (7th December 2022) - Rumondor, Pingkan C. B.; Randall, Ashley K.; Purwono, Urip; Muttaqin, Darmawan; Ginanjar, Adriana Soekandar
Abstract: In a country with collective cultural values like Indonesia, marriage is considered desirable. Despite the perceived importance of marriage, the divorce rate increases due to couple's experiencing stress from both outside and inside the relationship. This creates the urgency of a valid dyadic coping (DC) measurement for research and intervention. Current study aims to evaluate factor structure and validity of the Dyadic Coping Inventory (DCI)–Bahasa Indonesia in measuring the DC of married individuals living in Indonesia, and to evaluate measurement invariance between genders. Confirmatory factor analyses on 303 Indonesians supported the 5‐factor structure regarding self and partner, and 2‐factor structure common DC. Measurement invariance analyses found weak factorial gender invariance for self and perceived partner subscales, whilst strict gender invariance was found for common DC subscales of the DCI–Bahasa Indonesia test scores. Correlations between the DC–Bahasa Indonesia marital satisfaction and external stress demonstrated evidence of convergent and discriminant validity. Moreover, using 118 dyads subset data and multitrait‐multimethod approach, this study found good construct validity for several DC factors. Limitations and future directions are presented.